ANALYSES OF THE UNBORN CHILD SUPPORT LAW - Carolina Cerqueira Lopes, Fernanda; de Lelis Colani Barbosa, Camilo (Revista Gênero e Interdisciplinaridade, 2021)
The regulation of the unborn child support occured after the enactment of the law n.º 11.804/2008. The issue of child support has always been vastly discussed, especially when it is related to the rights of unborn children. The referred legal institut was therefore essential to support those rights. In this context, it is possible to identify the inconsistencies of this law. Certain discussions are still in vogue in this doctriary and jurisprudencial area, such as paternity evidences, active and passive legitimation, the inicial terme, the (non)retroactivity of unborn child support facing non concession and posterior proof of paternity, the (im)possibility of demanding compensation for material and/or moral damage concerning the “non-father”. It is linked thus to the fundamental rights and fundamental principles within the national legal core, such as human dignity, the right to life, the best interest of a child, responsible fatherhood, family solidarity and the legal position of unborn children.